Effect of organic solvents on cell-bound penicillin V acylase activity of erwinia aroideae (DSMZ 30186): a permeabilization effect - Kumar, Atul; Pundle, Archana (Journal of Molecular Catalysis B-Enzymatic, 2009)
Erwinia aroideae (DSMZ 30186) is a potential microbial culture to produce intracellular penicillin V acylase (PVA). The whole cell PVA activity was improved by permeabilization with various organic solvents. The cell-bound PVA activity showed an eightfold increase upon treatment with chloroform (5 mu L/mg(dry) (biomass)) for 10 min and diethyl ether (10 mu L/mg(dry) (biomass)) for 45 min. Hexane, toluene, ethyl acetate and dichloromethane enhanced the enzyme activity up to two-, six-, four- and two-fold, respectively; whereas, PVA activity declined drastically on permeabilization with acetone, pyridine and alcohols. The physicochemical properties of the organic solvents used for permeabilization were correlated with the change in activity. It was found that solvents with high hydrophobicity (log P > 0.68) and lower dielectric constant (< 9) were relatively effective in increasing PVA activity. These results allow systematic selection of suitable solvent for best performance. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: dielectric constant; Erwinia aroideae; Hydrophobicity; Organic solvents; Penicillin V acylase; Permeabilization